(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Today, a great emphasis is being placed on the production of new types of organic substances and composite products based on the waste of products produced in various industrial sectors, their conversion into secondary and intermediate raw materials through complex processing, and their use on a large scale. This, in turn, increases the demand for the products of this processing.